Academic Dishonesty in Modern Universities: A Review of Theoretical Approaches and Empirical Findings - Shmeleva, Evgeniia (Journal of Economic Sociology, 2015)
Academic dishonesty (e.g. cheating and plagiarism) is a pervasive and serious problem, which may jeopardize the quality of Russian educational system. Elaboration and implementation of preventive measures requires valid and reliable data on the reasons for students using unethical and dishonest strategies while enrolled in university. Nonetheless, there is no research on factors of academic dishonesty among Russian students. This article provides a review of foreign and Russian studies aimed at formulation of initial ideas about determinants and peculiarities of academic dishonesty, which may help formulate adequate hypotheses and research questions for the study of dishonest behavior among students of Russian universities. The paper enumerates the most popular approaches to the study of academic fraud: an economic approach based on G. Becker’s economic theory on crime and an approach rooted in the theory of planned behavior developed by I. Ajzen. Moreover, it describes the advantages and disadvantages of the most frequently applied methods for measuring factual academic dishonesty: direct question survey method and the surreptitious method. Findings about Russian academic dishonesty are also introduced. The latter part is devoted to a description of two groups of possible factors: individual and contextual.